فهرسة مخطوطات خزانة الشيخ محمد بن عيسى المرساوني الخاصة الليبية: المنهجية والمساهمات في دراسة التراث المخطوط الإباضي - المزاوي, علي بن يوسف (التراث المادي (الأثري والمخطوطات) وغرري المادي في ليبيا والدول المجاورة لها الوضعيات المعارصة والآفاق =Patrimoine matériel (archéologique et manuscrit) et immatériel en Libye et dans les pays voisins Situations contemporaines et perspectives, 2025)
Keywords: Bibliothèques -- Djebel Nefousa; Catalogue -- Djebel Nefousa; Manuscrits -- Djebel Nefousa

فهرست الوراق المخطوطات الليبية في شمال افريقيا - الشقروني, توفيق عياد (كتب بلا قيود, 2025)
Keywords: Bibliothèques -- Afrique du Nord; Manuscrits -- Djebel Nefousa

المخطوطات النفوسية في مكتبات وادي مزاب: دار إروان بغرداية أنموذج - عمي سعيد, عبد الفتاح; بابا نجار, إلياس حسين (مجلة شروس العلمية, 2024)
Keywords: Bibliothèques -- Mzab; Manuscrits -- Djebel Nefousa

The libraries of Nafusa Documentation and digitization of the written material heritage in the Jebel Nafusa, Libya - Mazawi, Ali; Tounsi, Slimane; Love Jr, Paul M. (Lecture Series, 2022)
In collaboration with the Centre for Studies and Research on Ibadism (Ibadica), Slimane Tounsi, President of Ibadica, Ali Mazawi, Coordinator of “The Libraries of Nafusa” project in Libya, and Paul Love, Professor of History and Academic Coordinator of “The Libraries of Nafusa" project, will offer a description of the planning, implementation, and future aims of the pilot project "The Libraries of Nafusa" (2021–2022), which sought to document and to digitize written material heritage in the Jebel Nafusa in Libya. “The Libraries of Nafusa” was a pilot project (2021–2022) to document and to digitize written material culture in the Jebel Nafusa region of Libya. It was led by the Ibadica, Centre for Studies and Research on Ibadism, in France and the Fassato Foundation in Libya, with financial support from the Gerda Henkel Stiftung “Patrimonies” funding program in Germany. The administrative team reflects the international nature of the project, with members based in Algeria, France, Morocco, Tunisia, and the United States.
Keywords: Bibliothèques -- Djebel Nefousa; Manuscrits -- Djebel Nefousa

‏فهرس مخطوطات خزانة الشيخ محمد بن عيسى بن سعيد المرساوني النفوسي الليبي (‏المتوفى حوالي منتصف قرن 14هـ)، دفين جزيرة جربة تونس - الحاج موسى, بشير بن موسى; المزاوي, علي بن يوسف (سلسلة فهارس مخطوطات نفوسة, 2024)
Keywords: Bibliothèques -- Djebel Nefousa; Catalogue -- Djebel Nefousa; Manuscrits -- Djebel Nefousa

Migrant Manuscripts in the Jebel Nafusa, Libya - Love Jr, Paul M. (Circulations: 17th Annual Lawrence J. Schoenberg Symposium on Manuscript Studies in the Digital Age, 2024)
Manuscripts produced and used by Ibadi Muslim communities have been on the move in the Maghrib and beyond for over a millennium. Yet most Ibadi texts, including most extant copies of pre-modern texts, were copied from the 18th century onward. This means that any study of these manuscripts must address their early modern and modern histories, including their encounter with colonialism, their role in shaping post-independence nationalist historiographies, and contemporary efforts at manuscript documentation in the region. In this presentation, I follow the history of manuscript migration connected to Ibadi communities in the Jebel Nafusa through four intersecting themes. The first relates to the objects themselves, pausing to consider the history of their production, based on a survey of manuscript catalogs and data from recent digitization and documentation projects in the region. This dimension has migration at its core, since many “Nafusi” manuscripts were produced outside the Jebel Nafusa in other centers of Ibadi learning in Northern Africa. Continuing to follow the manuscripts as they moved through space allows us to trace the trajectories of their copyists and owners. Using exemplary private libraries today located in Djerba, Tunisia, I present a migrant manuscript trajectories that connect the Jebel Nafusa, Cairo, the Mzab Valley in Algeria, and the island of Djerba. I then turn my attention to an important but often neglected aspect of Maghribi manuscript histories; namely, their colonial legacies. Finally, I highlight the work done by local Ibadi organizations in the past two decades to document and to preserve individually and collectively owned manuscript collections.
Keywords: Bibliothèques -- Djebel Nefousa; Manuscrits -- Djebel Nefousa

Projets de préservation du patrimoine matériel écrit dans le Jebel Nafusa (Libye) et à Djerba (Tunisie) - Love Jr, Paul M.; Boujdidi, Ali; Mazawi, Ali (Situations contemporaines des patrimoines archéologiques, manuscrits et culturels en Libye et au Maghreb: des richesses à préserver ?, 2023)
Keywords: Bibliothèques -- Djebel Nefousa; Bibliothèques -- Djerba; Manuscrits -- Djebel Nefousa; Manuscrits -- Djerba

Libraries of the Nafusa. A pilot project to document and digitize material heritage in the Jebel Nafusa, Libya - Love Jr, Paul M. (Revisiting the History of Medieval Libya (7th-16th centuries) Sources, Analyses, Projects, 2022)
Keywords: Bibliothèques -- Djebel Nefousa; Manuscrits -- Djebel Nefousa

تحليل بيانات بعض فهارس مخطوطات المدرسة الإباضية - الشقروني, توفيق عياد (Yakin Doğu Üniversitesi İlahiyat Fakültesi Dergisi, 2017)
Keywords: Manuscrits -- Djebel Nefousa

Aʿlām wa-Makhṭūṭāt fī ‘l-Turāth al-Islāmī al-Lībī - Umādī, Mūḥammad (2006)
Keywords: Manuscrits -- Djebel Nefousa